MERCHANDISING OF PERSONALITY RIGHTS: A Distinctive Sign for Business Models in the Fashion Field / MERCHANDISING DE DIREITOS DA PERSONALIDADE: Um Sinal Distintivo para Modelos de Negócios no Ramo da Moda - Araújo, Rosalina Corrêa de; Peralta, Patrícia; Aime, Bárbara (Revista Online de Pesquisa : Propriedade Intelectual, 2018)
This introductory study aims to assess the personality rights as a distinctive sign and also the construction of its protection in the intellectual property scope. It has been pursued to demonstrate that the merchandising of personality rights has been evolving to become a usual business model based on the commercial exploitation of fame that its holders have, therefore, reorienting the engagement of names related to luxury fashion.